2019
DOI: 10.1038/s41467-019-11704-w
|View full text |Cite
|
Sign up to set email alerts
|

Mapping eGFR loci to the renal transcriptome and phenome in the VA Million Veteran Program

Abstract: Chronic kidney disease (CKD), defined by low estimated glomerular filtration rate (eGFR), contributes to global morbidity and mortality. Here we conduct a transethnic Genome-Wide Association Study of eGFR in 280,722 participants of the Million Veteran Program (MVP), with replication in 765,289 participants from the Chronic Kidney Disease Genetics (CKDGen) Consortium. We identify 82 previously unreported variants, confirm 54 loci, and report interesting findings including association of the sickle cell allele o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(134 citation statements)
references
References 91 publications
7
122
2
Order By: Relevance
“…[50][51][52][53][54] Using large studies for discovery and algorithms that incorporate variants across the genome, our results showed a significant improvement in the performance of PRS compared with previous efforts for score development (7% vs. 1.7 to 2.8% of variance explained). [6][7][8][9][10][11] The phenotypic variance explained by the PRS was larger and in line with GWAS meta-analysis estimates. 5 We also observed a statistically significant link between the genetic basis of eGFR and a spectrum of incident kidney disease outcomes.…”
Section: Plasma Proteome As An Intermediate Traitsupporting
confidence: 82%
See 2 more Smart Citations
“…[50][51][52][53][54] Using large studies for discovery and algorithms that incorporate variants across the genome, our results showed a significant improvement in the performance of PRS compared with previous efforts for score development (7% vs. 1.7 to 2.8% of variance explained). [6][7][8][9][10][11] The phenotypic variance explained by the PRS was larger and in line with GWAS meta-analysis estimates. 5 We also observed a statistically significant link between the genetic basis of eGFR and a spectrum of incident kidney disease outcomes.…”
Section: Plasma Proteome As An Intermediate Traitsupporting
confidence: 82%
“…[1][2][3][4] Genomewide associations studies (GWAS) have grown rapidly in the last decade and identified numerous loci for kidney function, which gave rise to increasing attention to testing polygenic risk scores (PRS) as risk factors for kidney diseases risks. [5][6][7][8][9][10][11] However, previous PRS provided limited risk stratification for adverse kidney outcomes such as end-stage kidney disease (ESKD). 5,10 Potential reasons include: small sample sizes of early GWAS, which might lead to imprecise estimation of the associations between individual variants and disease risk; limiting the PRS to genetic variants that reached genome-wide significance (P < 5 × 10 −8 ); and a lack of deeply phenotyped data to identify cases.…”
Section: Intruductionmentioning
confidence: 99%
See 1 more Smart Citation
“…51,52 That being said, the EHBP1 gene has not been implicated in any Mendelian genetic disorders, whereas bi-allelic pathogenic variants in WDPCP have been shown to cause Bardet-Biedl syndrome, a disorder characterized, in part, by hepatic fibrosis and dyslipidemia, both phenotypes characterized by perturbed GGT and LDL cholesterol levels. 8,35 Replication of known associations Of the 27 significant gene-trait associations we identified that replicate previously-known associations from the literature, 11 have been reported as mapping to the ciliary candidate genes that we set out to study: CENPF with Creatinine, 53,54 CEP164 with HDL, 44,55 POC5 with Cholesterol LDL and HDL, 51,52,56,57 PROSER3 with HDL, 52 RP1 with Cholesterol and LDL, 51,58,59 RP1L1 with Triglycerides, 51,52 SDCCAG8 with Creatinine, 53,55,60 and SPATA7 with Creatinine 54 (Figures 2-3, S5-6, S22-23, S25-28 ). Our study adds further evidence to the hypothesis that these ciliary genes play in important role in affecting these laboratory phenotypes in the general population.…”
Section: Wdpcpsupporting
confidence: 60%
“…The DYNC2LI1 gene neighbors the genes ABCG5 and ABCG8, both known to be important in cholesterol metabolism, 51,52,59,63 while the IFT172 gene abuts the GCKR gene, which has been extensively associated with blood glucose, triglyceride, LDL, GGT, AlkPhos, and creatinine levels. 44,[51][52][53][54][64][65][66][67][68][69] We found the DYNC2LI1 locus to be significantly associated with LDL and total cholesterol, as has been previously published, but also found significant associations with A1c (most significant p-value 4.50e-13 for rs116520905), Creatinine (most significant p-value 1.14e-08 for rs116520905), and ALT levels (most significant p-value 4.29e-14 for rs56266464) -all of them previously unreported, and none of which replicated in our meta-analysis ( Figures 2-5). The DYNC2LI1 gene is known to be causative of two Mendelian ciliopathy syndromes, Ellis-van Creveld syndrome and short rib polydactyly syndrome, both syndromes sometimes characterized by kidney and liver disease.…”
Section: Dync2li1 and Ift172mentioning
confidence: 99%